A 16 fabry-perot optical-channels array for biological fluids analysis using white light - Minas, Graça (2003)
This paper describes a biosystem (biological system) used to measure the concentration of biological substances in urine, serum, plasma or cerebrospinal fluid. Rather than just one channel, it comprises 16 optical-channels that enable the measurement of the concentration of 16 different biological substances. An array of 16 optical filters based on Fabry-Perot thin-films optical resonators has been designed. Each optical-channel is sensitive in a single wavelength with a Full-Width-Half-Maximum (FWHM) of 7 nm. The filter fabrication requires only 4 masks, used with different etch time. A commercially available band-pass optical filter with a band-pass wavelength in 450-650 nm is used. The biosystem requires only a white light source for illumination due the use of selective optical filters.